2015
DOI: 10.1016/j.msard.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and comorbidities in patients with multiple sclerosis compared with a population without multiple sclerosis: An observational study using the US Department of Defense administrative claims database

Abstract: Rates of mortality and several comorbidities are higher in the MS versus non-MS cohort. Early recognition and management of comorbidities may reduce premature mortality and improve quality of life in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
87
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 29 publications
8
87
0
3
Order By: Relevance
“…Using the military British records (mostly males) proportional mortality ratios for MS in male members of the armed forces were found to be consistently elevated over 3 successive decades, 1979–2010, when compared to groups for each main social class and in other selected occupations [18]. Similarly, in a study by Capkun et al [17], a higher all-cause mortality was reported in those with MS (rate of 1.7–3.5-fold) when compared to a non-MS cohort, with 60.4% of the patients with MS who had received disease-modifying treatment in the past. A study that includes US-based individuals with MS, mortality risks were found to increase with age as well [17].…”
Section: Discussionmentioning
confidence: 95%
“…Using the military British records (mostly males) proportional mortality ratios for MS in male members of the armed forces were found to be consistently elevated over 3 successive decades, 1979–2010, when compared to groups for each main social class and in other selected occupations [18]. Similarly, in a study by Capkun et al [17], a higher all-cause mortality was reported in those with MS (rate of 1.7–3.5-fold) when compared to a non-MS cohort, with 60.4% of the patients with MS who had received disease-modifying treatment in the past. A study that includes US-based individuals with MS, mortality risks were found to increase with age as well [17].…”
Section: Discussionmentioning
confidence: 95%
“…Capkun et al. noted a slight decrease in melanoma rate among MS patients from a large sample, but do not report on melanoma risks among natalizumab‐treated MS patients 37. Another study reviewing incidence of cancer in MS (sampling 54,929 patients) concluded that melanoma rates were lower for people with MS compared to melanoma among the general population 26.…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting our findings, several factors, particularly epidemiology of melanoma, natalizumab‐associated progressive multifocal leukoencephalopathy (PML), various aspects of the TOUCH Risk Management (RiskMAP) Action Plan, and the Safety Surveillance Program in this RiskMAP (Table 3), potential pathophysiology, and an overview of pharmacovigilance efforts for opportunistic complications of medications, should be considered 6, 7, 8, 9, 10, 11, 13, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations